“Frizioni famigliari”. Lavoratori, salute e conflitti in un’area industriale siciliana - Andrea Filippo Ravenda (Archivio Antropologico Mediterraneo)
The essay focuses on local conflicts related to the presence of an oil refining plant in Milazzo, north-western Sicily. On the basis of an ethnographic research led in close contact with some refinery workers and some members of environmental justice movements, this paper highlights how the public assessments on the interweaving of industrial presence, environment and health, defined in conflicting “causation fields” produce real frictions inside the workers families. From this perspective, the families and the biographies of the workers themselves are spaces of friction useful for the understanding of the more complex system that connects global instances of environmental risk to local specificities and the experiences of the people who live and work in industrial areas.